SOME SUBORDINATION RESULTS ASSOCIATED WITH GENERALIZED RUSCHEWEYH DERIVATIVES - Juma, A. R. S.; Aziz, F. S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this paper, we consider an unified class of functions of complex order associated with generalized Ruscheweyh derivative. We obtain a necessary and sufficient condition for functions to be in this class.